Optimization of solid waste collection using RSM approach, and strategies delivering sustainable development goals (SDG’s) in Jeddah, Saudi Arabia - Neyara Radwan (Nature Portfolio, 2021)
Abstract The rapid industrial development, high population growth, and rapid urbanization of Saudi Arabia have led to increased pollution and waste levels. Every day, solid waste disposal for governments and local authorities becomes a significant challenge. Saudi Arabia produces over 15 million tonnes of solid waste annually, with a population of around 29 million. The waste production per person is estimated at between 1.5 and 1.8 kg per day per person. About 75% of the population in urban areas is concentrated, making it imperative that government steps are taken to boost the country's waste recycling and management scenario. The production of solid waste in Riyadh, Jeddah, and Dammam, three of the largest cities, exceeds seven million tonnes annually, which shows the enormity of the civic body problem. During this study, the design Expert software was involved in the optimization of process parameters during the collection of municipal solid waste (MSW) from Jeddah city. The use of design experiments and numerical optimization is quite effective in optimizing the different process parameters on the overall cost. Saudi Arabia has a critical need for a resilient waste system and agile waste management system to control its municipal solid waste quickly and environmentally friendly for achieve Saudi Vision 2030. For this study design of experiment, software was employed to optimize the cost per trip, thereby considering process parameters. It is therefore essential to examine the existing practices and future opportunities for solid waste collection, storage, and disposal. This study considered that MSW generated in Saudi Arabia which is having great potential to be converted into wealth. Hence, considering the current environment situation, energy prospective and future management strategies for MSW have also been reviewed.